A p.Arg499His Mutation in SPAST Is Associated with Infantile Onset Ascending Spastic Paralysis Complicated with Dysarthria and Anarthria - Ogasawara, Masashi; Saito, Takashi; Koshimizu, Eriko; Akasaka, Noriyuki; Sasaki, Masayuki (Neuropediatrics, 2019)
The complication of anarthria in hereditary spastic paraplegia (HSP) patients has been reported to result from mutations in either ALS2 or FA2H. Here, we present a case of a 12-year-old boy with hereditary spastic paralysis and anarthria associated with a SPAST mutation. Initial presentation was at 14 months of age, when the patient experienced leg stiffness. At 3 years of age, he could speak well using sentences. At 9 years of age, he was found to have dysarthria and had difficulty writing. At 12 years of age, the ability to speak was lost. The patient could not vocalize any words, despite contraction of his neck and respiratory muscles during attempted vocalization. Additionally, the patient has never walked independently in his life. Considering these symptoms, we diagnosed him as having infantile onset ascending hereditary spastic paralysis (IAHSP) complicated with anarthria. By whole-exome sequencing, we discovered a heterozygous SPAST mutation c.1496G > A (p.Arg499His), which was not found in the parents and is probably de novo. This mutation was already repeatedly described with similar phenotype. Our results suggest that the p.Arg499His mutation in SPAST should be considered as a differential diagnosis in IAHSP.
Keywords: anarthria; dysarthria; ascending spastic paralysis; SPAST